2022
DOI: 10.5817/cz.muni.m210-8643-2022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding unconventional medicine

Abstract: The phenomenon of unconventional medicine is an important feature of any contemporary society. Considering the increasing popularity of various forms of non-biomedical methods of healing among various groups of people, the necessity of an in-depth investigation of traditional, complementary and alternative therapies continues to grow. Existing terminology along with prevalence rates, legal status and historical development, vary greatly in European countries. The main reason behind the compilation of this publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…However, during the communist period, almost all kinds of unconventional health care were considered, to a great extent, as backward and superstitious practices. The ideological hegemony of Marxism, using a doctrine of materialism, led socialist governments in the Eastern Bloc to outlaw any kind of medical practice and ideas incompatible with scientific explanation (Souček & Hofreiter, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the communist period, almost all kinds of unconventional health care were considered, to a great extent, as backward and superstitious practices. The ideological hegemony of Marxism, using a doctrine of materialism, led socialist governments in the Eastern Bloc to outlaw any kind of medical practice and ideas incompatible with scientific explanation (Souček & Hofreiter, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…One study conducted prior to the COVID-19 pandemic, investigating the prevalence of unconventional medicine in Slovakia, revealed that 846 (82.4%) of the 1,027 survey participants reported using some kind of unconventional medicine on a regular basis, that is, at least once a year or several times during their life (Souček & Hofreiter, 2022a , b ). Approximately 20% of all users of unconventional medicine reported use of religious healing.…”
Section: Methodsmentioning
confidence: 99%